P-133 Is a therapy led rehabilitation for wellbeing service appropriate within a hospice setting?. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - English, Anne; Bristow, Catherine; Obita, George; Carter, Lucy; Haynes, Sarah; Sawyers, Nikki
Abstract : Background: Physical function and independence are important for patients with advanced illness and evidence suggests that maintaining autonomy, dignity, control and a sense of normality are priorities for them (Tiberini & Richardson, 2015). Aims: A recent benchmarking exercise demonstrated that our hospice needed to develop an earlier approach to rehabilitation (Tiberini & Richardson, 2015). Therefore, a Rehabilitation for Wellbeing Project was developed at Dove House Hospice in Hull aiming to: Identify patients earlier in their palliative pathway, raise awareness and improve accessibility to hospice care Demonstrate a rehabilitative approach that promotes physical function, confidence, independence and psychological well–being To show benefits to patients' and carers' wellbeing through audit Educate staff on the benefits of a rehabilitative approach to personalised patient care. Method: The group operates twice weekly for six weeks, offering educational and physical activities and is delivered by an experienced therapy team, assisted by volunteers. Educational topics include fatigue, breathlessness, mindfulness, nutrition and the benefits of exercise. Patients identify personal goals and share their experiences. Validated tools have been used to record outcomes, e.g. MYCAW (Measure Yourself Concerns and Wellbeing) and NRS (Numeric Rating Scale). Results: Referrals have been received from all health professionals and self -referrals were also accepted. Participants so far have given fantastic feedback with improvements in confidence, self-esteem, mood, physical function and quality of life. Conclusion: This innovative project has rejuvenated rehabilitation in palliative care within the hospice. Future plans: The group has evaluated exceptionally well so far and Dove House Hospice will continue to fund the rehabilitation for wellbeing project after the original project funding has ceased.